One for the money [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 1995)
Broke, desperate, and with few job prospects, Stephanie Plum starts working as a bounty hunter for her bail bondsman cousin. For her first assignment, she's asked to find Joe Morelli, an ex-cop accused of murder. Stephanie really wants to nail Morelli to the wall, not just for the reward, but because he used and abused her when she was just a teenager.